Peningkatan Pengetahuan Masyarakat Melalui Edukasi Penggunaan Antibiotik Yang Benar di Puskesmas Talang Banjar Kota Jambi - Elsa Marsellinda; Nabila Dwi Olivia; Tessa Amanda Primadhini; Anggelina Effendi; Mexsi Mutia Rissa (STIKes Ibnu Sina Ajibarang, 2025)
Antibiotic resistance is a worldwide threat that is largely caused by the inappropriate use of antibiotics. The purpose of this community service is carried out in order to increase knowledge about the wise and correct use of antibiotics. This community service was given to 20 patients with counseling using leaflets. In general, the implementation of this community service was categorized as successful and went well. There was an increase in knowledge about the importance of using antibiotics correctly after counseling.